Изучение роста кормовых растений в искусственных многовидовых сообществах - Кохан, Т.П. (Промышленная ботаника, 2002)
Specific features of perennial forage plants Arrhenatherum elatius (L.) J. et C. Presl, Dactylis glomerata L. Onobrychis viciifolia Scop. ‘Peschany 1251’ growth as monocultures, and also as three-, five- and seven- species variants has been revealed using the authors’ original scheme of sowing seeds in the shape of tetragonal and hexagonal (based on principle on honeycombs) lattice for five and three (or seven) species respectively. The dependence of Arrhenatherum elatius (L.) J. et C. Presl, Dactylis glomerata L. growth indeces on number of components in multispecific communities has been traced out. Such spacing of plants in artificial plant communities has proved useful.